The Legal Consequences of Passing Off Actions Involving the Registered Well-Known Trademark of Hugo Boss vs Anthony Tan - Made Aubrey Josephine Angelina; Ariawan Gunadi (Dinasti Research, 2024)
A trademark, as part of Intellectual Property Rights, is an important element for business operators to differentiate their products from those of other business operators. Passing off is one of the most common forms of trademark infringement, occurring when a business imitates a well-known trademark identically to create confusion among consumers. Famous brands have a high reputation and a good image in society, but the protection against passing off for famous brands is still lacking. In Law Number 20 of 2016 concerning Trademarks and Geographical Indications, there is still no clear regulation regarding the passing off of well-known trademarks, resulting in legal uncertainty for the original well-known trademark owners. As a result, violations of well-known brands frequently occur, driven by economic factors and societal stereotypes that view well-known brands as symbols of social status.